10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Sudden cardiac death (SCD) is a leading cause of mortality across the chronic kidney disease (CKD) continuum and becomes particularly prominent in dialysis-dependent kidney failure. In hemodialysis, SCD accounts for roughly one quarter to one third of all deaths and up to 60%-75% of cardiovascular mortality, with marked temporal clustering around the long interdialytic interval and the first post-interval session. Traditional views have emphasized descriptive epidemiology and presumed ventricular tachyarrhythmias. More recent device-based studies challenge this paradigm, revealing a heterogeneous arrhythmic spectrum in which bradyarrhythmias, pauses, and conduction system disease are often at least as frequent as sustained ventricular tachycardia or fibrillation. This narrative, non-systematic review synthesizes epidemiologic, mechanistic, and interventional data on SCD in CKD and dialysis, with particular emphasis on insights from implantable loop recorder and implantable cardioverter-defibrillator cohorts and on modifiable dialytic and pharmacologic factors. A framework for prevention is proposed around three interacting domains: the structural myocardial substrate, the electrophysiologic milieu, and dialysis-related triggers. Within this framework, contemporary heart failure and CKD therapies (including sodium-glucose cotransporter 2 inhibitors, angiotensin receptor-neprilysin inhibitors, mineralocorticoid receptor antagonists, and beta-blockers), individualized dialysis prescriptions (targeting potassium, calcium, bicarbonate, ultrafiltration, and scheduling), and selective use of device therapy are considered complementary components of mechanism-driven SCD prevention. Methodological challenges in defining and adjudicating SCD in CKD are discussed, and priorities are outlined for improved phenotyping, continuous rhythm monitoring, and CKD-specific risk stratification, with the overarching aim of moving from descriptive statistics to effective risk modification.